Challenges and Opportunities for Women Fishermen in Pamekasan: Gender Aspects in Family Resource Management - Aini, Qurrotul (Sakina: Journal of Family Studies, 2025)
This study aims to analyze the role of women fishermen in Pamekasan in managing family resources and the challenges they face in carrying out these roles. This study uses a qualitative method with in-depth interviews with women fishermen in Pamekasan who were selected purposively and analyzed using a gender analysis approach developed by Caroline O.N. Moser, which divides women's roles into three dimensions: productive, reproductive, and socio-community. The results of the study indicate that women fishermen play a significant role in managing family resources. In the productive dimension, they are involved in managing marine catches and side businesses, such as making salted fish or fish crackers. In the reproductive dimension, despite the large domestic burden, they are able to integrate household tasks with economic activities, maintaining family harmony. In the socio-community dimension, although more supportive, their involvement strengthens the solidarity of the fishing community. However, major challenges related to gender inequality hinder their dual roles. Women fishermen are often hampered by a lack of access to capital, training, and technology that increases business capacity. The heavy burden of domestic work limits the time and energy to develop economic capacity. Inequality in the division of domestic tasks worsens their emotional and mental well-being. On the socio-community side, despite their activeness, women are often isolated from wider social networks, with their social roles under-recognized. This study suggests more comprehensive empowerment measures to address these inequalities, including access to capital, training, and wider social networks.